Development of Universiti Teknologi Mara Sport Center Alumni Database (USCA) using distributed database approach in horizontal fragmentation technique / Norafiza Awalludin - Awalludin, Norafiza (2006)
After graduating from universities, every student becomes an alumnus. Currently, many alumni associations mainly organized around universities. The main of the associations is to share knowledge among alumni about their experiences that may support and advance the pursuit of academic excellence at the University. This research project is about developing UiTM Sport Center Alumni System (USCA) as web application and design distributed database for UiTM Sport Center. The main purpose is to gather, manage and sustain information about UiTM Sport Center alumni. The main problem for UiTM Sport Center is they do not have a database to store the alumni information and Staff of Sport Center difficult to maintain and updates the alumni profile. The objectives of the research are to construct the requirement, design distributed database using horizontal fragmentation technique and design a system solution. Requirement engineering process is used as a methodology for gathering information and data collection for system requirement. Top-down approach is use for design distributing database. In the end of the research project period, researcher found out that the result is comply with the objectives and therefore, all the objectives in these research project have been achieved.